Different implications of daytime and nighttime heart rate variability on total burden of cerebral small vascular disease in patients with nondisabling ischemic cerebrovascular events - Zhang, Zhixiang; Lv, Yijun; Wang, Qian; Wang, Yan; Zhang, Min; Cao, Yongjun (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to explore the relationship between total burden of cerebral small vessel disease (CSVD) and daytime and nighttime heart rate variability (HRV) parameters. Method Consecutive patients with nondisabling ischemic cerebrovascular events were recruited from the cerebrovascular disease clinic of Changzhou Second People's Hospital between January 2022 and June 2023. A total of 144 enrolled participants were divided into a mild CSVD group (74 patients) and a moderate-to-severe CSVD group (70 patients) based on total burden of CSVD. Various HRV parameters measured during 24-h, 4-h daytime, and 4-h nighttime periods (including natural log–transformed [ln] root mean square of successive RR interval differences [RMSSD], ln absolute power of the high-frequency band [0.15–0.4 Hz] [HF], ln absolute power of the low-frequency band [0.04–0.15 Hz][LF], and LF-to-HF ratio [LF/HF]) were then assessed in the 2 groups. Spearman correlation analysis was used to assess the correlation between total burden of CSVD and HRV parameters. HRV parameters with P-value < 0.05 in correlation analysis were included in the multivariable logistic regression analysis, and restricted cubic spline analysis was performed to assess dose-response relationships. Results Daytime 4-h lnRMSSD (r = –0.221; P = 0.008) and 4-h lnHF (r = –0.232; P = 0.005) were negatively correlated with total burden of CSVD, and daytime 4-h lnLF/HF (r = 0.187; P = 0.025) was positively correlated with total burden of CSVD. There was no correlation between nighttime HRV parameters and total burden of CSVD. After adjustments were made for potential confounders, daytime 4-h lnRMSSD (OR = 0.34; 95% CI: 0.16–0.76), 4-h lnHF (OR = 0.57; 95% CI: 0.39–0.84), and 4-h lnLF/HF (OR = 2.12; 95% CI: 1.18–3.82) were independent predictors of total burden of CSVD (all P < 0.05). S-shaped linear associations with moderate-to-severe total burden of CSVD were seen for daytime 4h-lnRMSSD (P for nonlinearity = 0.543), 4-h lnHF (P for nonlinearity = 0.31), and 4-h lnLF/HF (P for nonlinearity = 0.502). Conclusion Daytime parasympathetic HRV parameters are independent influencing factors of total burden of CSVD and may serve as potential therapeutic observation indicators for CSVD.